COLLABORATIVE JOURNALISM IN ALTERNATIVE MEDIA TO REPORT THE MARGINALIZED ISSUE: Case Study Collaborative Journalism in Project Multatuli of Alternative Media in Indonesia - Pamungkas, Andreas Tri; Pramesti, Olivia Lewi (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
Marginalized issue in the media doesn’t get portion in the mainstream media. Marginalized issue is the unprofitable for mainstream media because it brings the minimal profit. Moreover, the phenomenon of online media users in Indonesia is dominated by generation milineal dan generation Z. They are prefer reading the unqualified content than the qualified. As a result, the margininalized issue doesn’t get the interest for them. This research aims to see how the alternative media practice practice the collabolarative journalism to report the marginalized issue. Meanwhile, the alternative media places a portion of the news coverage on marginalized issue in the form of of indepth reporting. The alternative media in Indonesia is funded by funding such as NGOs, or research institutions to conduct the news production. Funding supports the alternative media because they lack of human resources and the media operating cost. This research used qualitative research with a case study approach. Researcher used the indept interview technique to gather the data. Researcher interviewed with the editorial team of Multatuli Project. The results of the study stated that the marginilized is a routine issue that published by the alternative media. Project Multatuli has chosen the marginalized issue because it encourage the society to aware for the this issue, particularly in Generation Milineal and generation Z. Project Multatuli wanted to develop the critical thinking from society in this issue. Furthermore, Project Multatuli has improved the collaboration between citizen and alternative media to find the solution about the marginalized issue in Indonesia. The data also showed that project Multatuli hasn’t used the rating approach to measure the traffic their news. Furthermore, the collaborative journalism has practiced by some parties, namely professional, individuals, NGOs, or other organizations that are interested with the marginalized issue. The party involved has done the reporting news collectively. On the process of making the indept news, they have shared the idea, interview with the source, and written the news. The whole of process of collaboration reporting has funded by donor that are also interested in the issue. Meanwhile, the parties who involved the collaboration reporting was responsible to disseminate the report of news to society through media channels and non media channels such us public discussions. This research has proved that alternative media still carries principle of the media as a watchdog, and facilitates society to discuss the marginalized issue. This research also stated that in the digitalization era, alternative media can still survive without using a rating approach.